As memórias de "um maestro demasiado humano": museologia e as correspondências de Waldemar Henrique - NASCIMENTO, Sônia Regina Silva do (2019)
This research has the purpose to rediscover the maestro Waldemar Henrique (1905-1995) through the letters written by him. In 1995, after his death, the letters were donated for the Government of the State of Pará with more than 15,000 pieces. At first, the collection was trusted to the Theatro da Paz, but in 1998, the collection was under the responsibility of the State Museum of Pará. Officially, in 2005, it was donated to the Museu da Imagem e do Som e ao Sistema Integrado de Museus e Memoriais (Museum of Image and Sound and the Integrated System of Museums and Memorials).The maestro was an internationally recognized musician. On March 23, 2010, the Waldemar Henrique DVD Collection was released with part of the Maestro collection in the city of Belém. The study focuses on the letters sent to his friends and family. The maestro had the habit of writing letters during his personal trips and artistic tours. Fifty-nine letters of his collection can been accessed in his DVD Collection. In Anthropology, relations are based on the theme of intersubjectivity and patrimony; History is tangled up for bringing debates and contributions concerning memory; Literature is touched, for letters are narratives in which the real, the fictional and the poetic are combined; and Museology is projected by proposing a specific listing and a thematic categorization form, according to current research contributions. Through this multidisciplinary look, this work will be a reflection and a resignification about the place of the personal objects in the maestro’s life, seeking their values, their potential to revert their meanings in emotions and memories. In addition, we propose that all content on this DVD should be available in the internet.